EARLY CRUSTAL BUILDING PROCESSES ON THE MOON: MODELS FOR THE PETROGENESIS OF THE MAGNESIAN SUITE - Shearer C.K.; Papike J.J. (My University, 2005)
The plutonic rocks of the magnesian suite (Mg-suite) represent the period of lunar basaltic magmatism and crustal growth (∼4.46 to 4.1 Ga) that immediately followed the initial differentiation of the Moon by magma ocean (LMO) formation and crystallization. The volume and distribution of the Mg-suite and its petrogenetic relationship to latter stages of lunar magmatism (mare basalts) remains obscure. These plutonic rocks exhibit a range of compositions and include ultramafics, troctolites, spinel troctolites, norites, and gabbronorites. A distinguishing characteristic of this suite is that they contain some of the most magnesium-rich phases (Fo95–90) that had crystallized from lunar magmas, yet they also are significantly enriched in an incompatible element component referred to as KREEP (a late-stage product of LMO crystallization containing abundant potassium (K), rare earth elements (REE), phosphorous (P), uranium, and thorium). Ion microprobe analyses of individual mineral phases (olivine, pyroxene, and plagioclase) from the Mg-suite have shown some very unexpected characteristics that have profound implications on the origin of these basaltic magmas. Although the Mg-suite lithologies are typified by silicates with relatively high Mg′, early liquidus phases such as olivine are fairly low in Ni, Co, and Cr relative to more iron-rich olivines in the younger mare basalts. The high Y and Ti/Y in early phases such as olivine and orthopyroxene indicate that the parental basaltic melts were high in incompatible elements and contained an “ilmenite fractionation” signature. However, the Y in olivine from many of the troctolites and ultramafic lithologies are only slightly greater than that of the olivine in the mare basalts whereas olivine in the norites, gabbronorites, and Apollo 14 troctolites are exceedingly high. The KREEP component may have been added to the Mg-suite parent magmas by assimilation or mixing into the mantle source. The volume of KREEP required to be added to the parental magmas of the Mg-suite tends to favor the latter mechanism for KREEP incorporation. The extremely high abundances of KREEP in the norites and gabbronorites are a product of substantial crystallization (40% to 70%) of KREEP-enriched Mg-suite parental magmas. Basaltic magmatism associated with KREEP extended for over 1.5 billion years and appears to have changed over time. The early stages of this style of lunar magmatism (Mg-suite) appear to represent melting of early LMO cumulates with low abundances of Ni, Co, Cr, and V. Later stages of KREEP-rich basaltic magmatism seemed to clearly involve melting of a variety of LMO cumulate assemblages with higher incompatible element enrichment. It appears that the heat derived from the KREEP component was instrumental in at least initiating melting of the lunar mantle over this period of time.